2022
DOI: 10.5009/gnl210177
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Alteration Influences Colorectal Cancer Metastasis to the Liver by Remodeling the Liver Immune Microenvironment

Abstract: Background/Aims This study aimed to explore the effect of gut microbiota-regulated Kupffer cells (KCs) on colorectal cancer (CRC) liver metastasis. Methods A series of in vivo and in vitro researches were showed to demonstrate the gut microbiota and its possible mechanism in CRC liver metastasis. Results Fewer liver metastases were identified in the ampicillin-streptomycin-colistin and col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…vaginae . Supplementation of Proteus mirabilis could promote CLM in mice by diminishing the proportion of Kupffer cells in the liver ( 60 ). In vitro experiments further proved that P. mirabilis promoted CRC cell migration by repressing Kupffer cell proliferation.…”
Section: The Gut Microbiota and Innate Immunitymentioning
confidence: 99%
“…vaginae . Supplementation of Proteus mirabilis could promote CLM in mice by diminishing the proportion of Kupffer cells in the liver ( 60 ). In vitro experiments further proved that P. mirabilis promoted CRC cell migration by repressing Kupffer cell proliferation.…”
Section: The Gut Microbiota and Innate Immunitymentioning
confidence: 99%
“…After co-culture with Proteus vulgaris and Proteus mirabilis , SNAI1 and VIM gene expressions had changed significantly in human colon cancer cell line Caco2, which are related to epithelial mesenchymal transformation, thus it was suggested that Proteus may be correlated with the epithelial mesenchymal transformation of CRC [ 21 ]. Moreover, increased abundance of Proteus mirabilis played a key role in the liver metastasis of CRC, which may count on the reduction of Kupffer cells in the liver [ 22 ]. Parabacteroides was observed to be distinctly higher in abundance in CRC tissues than normal mucosa adjacent to cancer [ 23 ], besides, CRC patients with high Parabacteroides expression in gut had observably poorer prognosis than CRC patients with low Parabacteroides expression in gut [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yuan N et al. ( 21 ) demonstrated that alterations in gut microbiota composition could remodel the liver immune microenvironment by regulating Kupffer cells (KCs) on colorectal cancer, promoting or inhibiting liver metastases. Alice Bertocchi et al.…”
Section: Discussionmentioning
confidence: 99%